Nitrogenase Activity Vis-a-vis Field Testing of Dalbergia sissoo Rhizobium Isolates Collected from Different Sources - Pandey, P. C.; Chaukiyal, S. P.; Pokhriyal, T. C. (Indian Forester, 1999)
Dalbergia sissoo Rhizobium isolates were collected from different sources viz., Asharori, Lachhiwala, Allahabad, Maldevta, Ramnagar, Chichrauli, F.R.I. Dehra Dun and pure culture from Microbiology Laboratory, Chandigarh to study their nitrogen fixation behaviour. Maximum in-situ nitrogenase activity was recorded in Asharori culture and minimum in Chichrauli. Six cultures were inoculated to Dalbergia sissoo seedlings, to study their symbiotic performances under potculture conditions. Maximum nodule number, its fresh and dry weight per plant and plant height was recorded in Asharori inoculated culture. Whereas, maximum nitrogenase (g-1h1 and pl-1h-1) activity was recorded in Maldevta and Microbiological Laboratory, Chandigarh cultures respectively inoculated to Dalbergia sissoo seedlings. No relationship was observed between in-situ and symbiotically associated Rhizobium strains in nitrogen fixation activity.